Structure-Function Relationships in Lactate Dehydrogenase - Adams, Margaret J. (1973)
The binding of coenzyme and substrate are considered in relation to the known primary and tertiary structure of lactate dehydrogenase (EC 1.1.1.27). The adenine binds in a hydrophobic crevice, and the two coenzyme phosphates are oriented by interactions with the protein. The positively charged guanidinium group of arginine 101 then folds over the negatively charged phosphates, collapsing the loop region over the active center and positioning the unreactive B side of the nicotinamide in a hydrophobic protein environment. Collapse of the loop also introduces various charged groups into the vicinity of the substrate binding site. The substrate is situated between histidine 195 and the C4 position on the nicotinamide ring, and is partially oriented by interactions between its carboxyl group and arginine 171. The spatial arrangements of these groups may provide the specificity for the L-isomer of lactate.